Gender differences in hockey players during on-ice graded exercise - Durocher, J. J.; Jensen, D. D.; Arredondo, A. G.; Leetun, D. T.; Carter, J. R. (The Journal of Strength and Conditioning Research, 2008)
The purpose of this study was to examine whether gender differences exist for ventilatory threshold (VT), lactate threshold (LT), and VO2max during on-ice skating in college hockey players. Ten male and 10 female Division III college hockey players performed a graded exercise skating protocol until reaching volitional fatigue. The graded exercise test employed stages that were 80 seconds in duration, with 40 seconds of rest between each stage to obtain blood lactate samples. Ventilatory threshold occurred at a higher percentage of maximal heart rate (HRmax) in women than in men. The women's VT occurred at 77.3% +/- 1.6% HRmax, while the men's VT occurred at 72.6% +/- 2.0% HRmax (p < 0.02). Men and women had similar HRmax values: 191.3 +/- 2.5 b/min and 185.8 +/- 2.5 b/min, respectively. VO2max was different between genders, with men at 52.7 +/- 1.3 mL/kg.min and women at 40.1 +/- 1.0 mL/kg.min (p < 0.01). In addition, VT was different between genders when measured as a percentage of VO2max, with men at 52.7% +/- 3.2% and women at 67.3% +/- 4.0% (p < 0.02). In contrast, LT was similar between genders when expressed as a percentage of HRmax or VO2max. For each gender, LT occurred at a significantly higher percentage of HRmax or VO2max than VT did. It can be concluded that VT does not accurately predict LT in male or female hockey players. Additionally, competitive female hockey players have a lower VO2max but a higher VT than their male counterparts. An increased VT may be a compensatory mechanism to offset the smaller VO2max values measured in female hockey players. On-ice testing is a practical way to address specific aerobic training needs of hockey players.